Exploring lifelong literacy learning in digital gameplay among midlife-to-older adults - Shen, Yanan; Ab Jalil, Habibah (Routledge, 2025)
The evolving communicative landscape and the aging population have rendered lifelong literacy learning increasingly significant among middle-aged and older adults. However, insufficient empirical studies have probed how to address and sustain such learning in late adulthood. This qualitative case study explored the possibilities and driving factors of midlife-to-older adults’ long-term digital gameplay for lifelong literacy learning. Data were collected from three participants with over a decade of gameplay experience through three rounds of interviews and observations across 10 months. The findings from the thematic analysis revealed that digital gameplay provided midlife-to-older adults with continuous opportunities to enhance proficiency in digital multimodal communication, cultivated multi-skills and multidisciplinary knowledge in situated practices, and encouraged intergenerational communication in affinity groups. Moreover, three main factors drove their long-term digital gameplay for sustainable literacy learning: continuous social support, a long-lasting desire for pleasure to combat idleness and stable access to suitable games. This study underscores that digital gameplay empowers midlife-to-older adults’ lifelong literacy learning featuring long-lasting progress, profound effects, and minimum cost. It offers a new theoretical lens to contextualize lifelong literacy in game-based learning contexts and promotes older adults’ lifelong literacy learning in informal contexts, thus making it more accessible and sustainable.